Assistive technology policy: a position paper from the first global research, innovation, and education on assistive technology (GREAT) summit. (4th July 2018) - MacLachlan, Malcolm; Banes, David; Bell, Diane; Borg, Johan; Donnelly, Brian; Fembek, Michael; Ghosh, Ritu; Gowran, Rosemary Joan; Hannay, Emma; Hiscock, Diana; Hoogerwerf, Evert-Jan; Howe, Tracey; et al.
Abstract: Increased awareness, interest and use of assistive technology (AT) presents substantial opportunities for many citizens to become, or continue being, meaningful participants in society. However, there is a significant shortfall between the need for and provision of AT, and this is patterned by a range of social, demographic and structural factors. To seize the opportunity that assistive technology offers, regional, national and sub-national assistive technology policies are urgently required. This paper was developed for and through discussion at the Global Research, Innovation and Education on Assistive Technology (GREAT) Summit; organized under the auspices of the World Health Organization's Global Collaboration on Assistive Technology (GATE) program. It outlines some of the key principles that AT polices should address and recognizes that AT policy should be tailored to the realities of the contexts and resources available. AT policy should be developed as a part of the evolution of related policy across a number of different sectors and should have clear and direct links to AT as mediators and moderators for achieving the Sustainable Development Goals. The consultation process, development and implementation of policy should be fully inclusive of AT users, and their representative organizations, be across the lifespan, and imbued with a strong systems-thinking ethos. Six barriers are identified which funnel and diminish access to AT and are addressed systematically within this paper. We illustrate an example of good practice through a case study of AT services in Norway, and we note the challenges experienced in less well-resourced settings. A number of economic factors relating to AT and economic arguments for promoting AT use are also discussed. To address policy-development the importance of active citizenship and advocacy, the need to find mechanisms to scale up good community practices to a higher level, and the importance of political engagement for the policy process, are highlighted. Policy should be evidence-informed and allowed for evidence-making; however, it is important to account for other factors within the given context in order for policy to be practical, authentic and actionable. Implications for Rehabilitation: The development of policy in the area of asssitive technology is important to provide an overarching vision and outline resourcing priorities. This paper identifies some of the key themes that should be addressed when developing or revising assistive technology policy. Each country should establish a National Assistive Technology policy and develop a theory of change for its implementation.